Effect of foot orthoses on running economy and foot longitudinal arch motion in runners with flat-arched feet - Crago, D.; Arnold, J. B.; Bishop, C. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To determine the effect of manipulating foot longitudinal arch motion with different-stiffness foot orthoses on running economy (RE) in runners with flat-arched feet and if changes in arch deformation and recoil were associated with changes in RE.